Integrating Artificial Intelligence in English Learning: Implementation of Duolingo Application to Improve English Skills - Firdausia, Wardaniatul; Zainuddin; Hamdani, Beny (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aims to evaluate the effectiveness of using the artificial intelligence (AI)-based application Duolingo in improving the English language skills of grade X A students at Madrasah Aliyah Darut Tauhid. This study used a descriptive method involving 29 students as samples. Data were collected through interviews, observations, and questionnaires which were analyzed using descriptive analysis for qualitative data and simple statistical analysis for quantitative data. The results showed that the use of Duolingo significantly helped students improve their vocabulary and speaking skills, as revealed through interviews. Observations showed consistent usage patterns, with effective study duration several times a week. Analysis of questionnaire data revealed that students showed high enthusiasm, found the app effective, were motivated and engaged in learning. Nonetheless, students also identified advantages and disadvantages of the app, including limitations of features that do not fully support productive skills such as speaking. This research makes an important contribution to the literature related to AI-based learning and educational practice, by emphasizing the need for integration of apps like Duolingo into the curriculum to increase student motivation and engagement. However, this study has limitations in terms of population coverage, study duration, and perceptual measurement.